2021
DOI: 10.1021/acs.inorgchem.1c03011
|View full text |Cite
|
Sign up to set email alerts
|

The Ruthenium Nitrosyl Moiety in Clusters: Trinuclear Linear μ-Hydroxido Magnesium(II)-Diruthenium(II), μ3-Oxido Trinuclear Diiron(III)–Ruthenium(II), and Tetranuclear μ4-Oxido Trigallium(III)-Ruthenium(II) Complexes

Abstract: The ruthenium nitrosyl moiety, {RuNO} 6 , is important as a potential releasing agent of nitric oxide and is of inherent interest in coordination chemistry. Typically, {RuNO} 6 is found in mononuclear complexes. Herein we describe the synthesis and characterization of several multimetal cluster complexes that contain this unit. Specifically, the heterotrinuclear μ 3 -oxido clusters [Fe 2 RuCl 4 (μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 128 publications
0
4
0
Order By: Relevance
“…To verify that the observed geometric differences did not stem from crystal packing effects, the DFT-optimized conformations of these complexes in vacuum were also inspected (for details, see Section S6); relevant geometrical parameters, also shown in Figure , gratifyingly agreed with the observed experimental tendencies. To gain further insight on this matter, topological analyses of the electronic charge density, ρ­( r ), and its Laplacian, ∇ 2 ρ­( r ), were carried out within the framework of Bader’s Quantum Theory of Atoms-in-Molecules (QTAIM), , a rigorous method employed in the study of covalent and noncovalent interactions; the data for relevant bond critical points (BCP) lying along the Ru-NO (BCP1) and N–O (BCP2) bond paths, are gathered in Table , where low positive values of ∇ 2 ρ­( r ) at BCP1 are in good agreement with the Ru-NO bond lying in between a covalent and a closed-shell interaction, whereas negative values at BCP2 reflect the covalent nature of the N–O bond; perhaps the most important information from these analyses is the differences in ρ­( r ) for both complexes at these BCPs, as electron density at the BCP correlates with bond strengths; the obtained values indeed show that the Ru–NO and N–O bonds are stronger and weaker, respectively, for acac-RuNO , as expected; moreover, the low ellipticity (ε) at BCP2 for both complexes is indicative of a cylindrical distribution of electron density around the N–O axis, resembling related linear ruthenium and iron nitrosyls and depicting a dominant triple bond character; it should be noted, however, that ε at this BCP is ca. 8 times higher for acac-RuNO, evidencing the slight deviation of the nitrosyl from the triple bond character as a consequence of the stronger Ru–NO π-backbonding.…”
Section: Results and Discussionmentioning
confidence: 99%
“…To verify that the observed geometric differences did not stem from crystal packing effects, the DFT-optimized conformations of these complexes in vacuum were also inspected (for details, see Section S6); relevant geometrical parameters, also shown in Figure , gratifyingly agreed with the observed experimental tendencies. To gain further insight on this matter, topological analyses of the electronic charge density, ρ­( r ), and its Laplacian, ∇ 2 ρ­( r ), were carried out within the framework of Bader’s Quantum Theory of Atoms-in-Molecules (QTAIM), , a rigorous method employed in the study of covalent and noncovalent interactions; the data for relevant bond critical points (BCP) lying along the Ru-NO (BCP1) and N–O (BCP2) bond paths, are gathered in Table , where low positive values of ∇ 2 ρ­( r ) at BCP1 are in good agreement with the Ru-NO bond lying in between a covalent and a closed-shell interaction, whereas negative values at BCP2 reflect the covalent nature of the N–O bond; perhaps the most important information from these analyses is the differences in ρ­( r ) for both complexes at these BCPs, as electron density at the BCP correlates with bond strengths; the obtained values indeed show that the Ru–NO and N–O bonds are stronger and weaker, respectively, for acac-RuNO , as expected; moreover, the low ellipticity (ε) at BCP2 for both complexes is indicative of a cylindrical distribution of electron density around the N–O axis, resembling related linear ruthenium and iron nitrosyls and depicting a dominant triple bond character; it should be noted, however, that ε at this BCP is ca. 8 times higher for acac-RuNO, evidencing the slight deviation of the nitrosyl from the triple bond character as a consequence of the stronger Ru–NO π-backbonding.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Several heterometallic complexes have been synthesized and characterized by spectroscopic methods ( 1 H NMR, UV-vis, IR in the solid state in the absence and under light irradiation), magnetochemistry and Mössbauer spectroscopy. 26 The results of SC-XRD studies of these complexes are shown in Fig. 10.…”
Section: Perspective Dalton Transactionsmentioning
confidence: 99%
“…24,25 Such systems may allow for light induced linkage isomerization, which will trigger changes in magnetic behavior leading potentially to novel functional materials. 26 Herein we will briefly discuss the most common synthetic routes towards ruthenium nitrosyl complexes with a variety of ligands and the compounds often used as starting materials (section 2). Several examples of preparation of related chalcogenonitrosyl complexes will be also presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation